2014
DOI: 10.3389/fnagi.2014.00147
|View full text |Cite
|
Sign up to set email alerts
|

Intraindividual variability across cognitive tasks as a potential marker for prodromal Alzheimer’s disease

Abstract: Recent studies have shown that increased cognitive intraindividual variability (IIV) across accuracy scores from tests representing different cognitive domains (across-domain IIV) might indicate prodromal Alzheimer’s disease (AD). Although IIV has been proposed to index cognitive control processes, IIV across accuracy scores from cognitive control tasks (within-domain IIV) has not been examined in healthy controls subjects (HCS), mild cognitive impairment (MCI), and AD patients in a single comparative study. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
42
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 49 publications
4
42
1
Order By: Relevance
“…Our findings are consistent with previously reported empirical evidence 9, 10, 13–15, 17 and showed there was slowed mean RT and elevated intra-individual variability in disease-specific NCD, despite having limited utility in differentiating between subtypes. Additionally, a combination of the two measures could differentiate between patients with different cognitive status.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings are consistent with previously reported empirical evidence 9, 10, 13–15, 17 and showed there was slowed mean RT and elevated intra-individual variability in disease-specific NCD, despite having limited utility in differentiating between subtypes. Additionally, a combination of the two measures could differentiate between patients with different cognitive status.…”
Section: Discussionsupporting
confidence: 93%
“…This type of variability is a universal feature that progressively increases during the ageing process 9, 10 . Thus, elevated intra-individual variability has been found in individuals with MCI 1113 , amnestic MCI 14 , Alzheimer’s disease 15 and mild dementia 16 relative to age-matched healthy controls. The increased intra-individual variability of RT is an independent marker that can predict the conversion from the pre-clinical stage to clinical dementia 17, 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Effects of dual-tasking on cognition were first assessed by the interaction between group and task condition (single versus dual task) in regard to the mean output across three trials, with the expectation that dual tasking would result in a steeper cost to cognition for the PD group than the NC group. Next, variability across the three single-task and dual-task trials was assessed, as intra-individual variability provides an index of cognitive dysfunction (Kälin et al, 2014; MacDonald, Li, & Bäckman, 2009; Sliwinski & Buschke, 2004). We expected that compared to NC, PD would show a greater increase in cognitive variability on dual task, reflecting instability in cognitive output while dual tasking.…”
Section: Introductionmentioning
confidence: 99%
“…Duchek et al (2009) also did not find significant differences in IIV between healthy APOE-ε4 carriers and non-carriers using three different selective attention tasks, except for a single score on incongruent trials of the Stroop task. Kalin et al (2014) reported a very small effect size difference between healthy elders with the APOE-ε4 allele compared to those without the allele for within-domain IIV in tasks of executive functioning. Nevertheless, longitudinal data is necessary to more clearly determine the predictive value of IIV for progression to the MCI stage and dementia.…”
Section: Discussionmentioning
confidence: 95%
“…No significant differences in overall IIV measures were reported between the healthy APOE-ε4 carrier and non-carrier groups, with the one exception being an IIV measure derived from Stroop incongruent trials. In a more recent study, Kalin et al (2014) examined within- and across-domain IIV in healthy elders with and without the APOE-ε4 allele, individuals with MCI, and those diagnosed with AD. Measures spanning several cognitive domains, including working memory, semantic memory, and executive functioning were examined.…”
Section: Introductionmentioning
confidence: 99%